Affective Commitment and Organizational Citizenship Behavior: Perceived Organizational Support as Mediation - Dymas Bagus Bimantara; Adi Rahmat; Helwen Heri (SAINS ORGANISASI, 2022)
This study aims to see how affective commitment has a dominant influence on organizational citizenship behavior through perceived organizational support for members of the Kampar Police. This type of research is explanatory research. The population is the Pekanbaru District Court Office, totaling 116 members of the Kampar Police. Data analysis in this study used SEM-PLS. Based on the data processing, it is found that there is an effect of the better perceived organizational support caused by the better affective commitment, which tends to improve organizational citizenship behavior. The findings of this study are that perceived organizational support is stated to be able to mediate the effect of affective commitment on organizational citizenship behavior of members of the Kampar Police Station. The limitation of this study is the lack of population size used. So it is suggested to further researchers to develop a population so that the results can be generalized.